The Roles and Importance of Promotion Tools and Destination Attributes of Mice Tourism on Jordan's Destination Image Formation - Alananzeh, Omar Abedalla Ahmed (2012)
The image of the destination has a significant role on tourists’ travel decision and selection of the destination to visit. Various approaches and strategies have been utilised by most of the countries to develop their destination image. However, in the context of Jordan less emphasis was given to develop a touristic image. Thus, strategies used in forming a destination image were vague and less effective. The objectives of this study are to investigate the roles of promotion tools and Meetings, Incentive travel, Conferences, and Exhibitions (MICE) destination attributes on touristic image formation and to identify the perceptions of MICE participants on the importance of promotion tools, MICE destination attributes, and destination image. A quantitative approach was employed in this study and several hypotheses were formulated based on the existing literature, push-pull theory, and models of destination image formation. A structured questionnaire was administered to 857 respondents who were selected through cluster random sampling technique. Data were collected from participants of MICE tourism in the cities of Amman and the Dead Sea. The findings of the study revealed that there were significant differences in respondents’ perceptions on the importance of MICE destination attributes, promotion tools, and destination image. Regression analyses indicated that MICE destination attributes and the roles of promotion tools positively influence destination image formation. Nevertheless, amenities showed the highest influence of MICE destination attributes on destination image formation, followed by ancillary services, accessibility, attractions, and activities. Meanwhile, affordability portrayed the lowest influence of MICE destination attributes on the overall touristic image formation of Jordan. The study has contributed to the body of knowledge with the proposed model that reveals the significant contribution of MICE destination attributes and the roles of promotion tools to the destination image formation of Jordan. Whereas, for the managerial implications, this study is able to provide guidelines and suggestions on marketing strategies to the public and the private sectors in order to enhance and develop MICE industry in Jordan as an international destination image.